IMPLEMENTASI UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK DAN DAMPAKNYA TERHADAP KEKERASAN BERBASIS GENDER ONLINE DALAM PERSPEKTIF FEMINISME - Azzahra Salsabilla (2023)
Komnas Perempuan announced that the case of Online Gender-Based Violence (OGBV) has become a new model of violence against women in the last three years in Indonesia. Some of them are the result of being ensnared by using the ITE Law. The ITE Law is a policy that regulates cyber security, but its emergence has become a problem because it is detrimental to victims of OGBV, especially women. This study aims to explain that the ITE Law does not take sides with women so that women have become multiple victims in the enforcement of the ITE Law. Researchers used feminist policy analysis, the concept of OGBV, and the concept of public policy to analyze the research. This research paradigm uses postpositivism with qualitative research methods and feminist case studies. The data collection technique that the researchers used was in-depth interviews with a member of Komnas Perempuan, SAFENet, and two members of LBH APIK Jakarta. The results of the study show that the ITE Law has become a tool to criminalize OGBV victims and does not take sides against OGBV victims. The ITE Law also does not adhere to feminist values so that many women are harmed by the ITE Law. The ITE Law also indirectly increases the number of OGBV cases. In this way, the ITE Law has had a very severe negative impact on victims of OGBV who should receive legal protection.